Silybum marianum total extract, silymarin and silibinin abate hepatocarcinogenesis and hepatocellular carcinoma growth via modulation of the HGF/c-Met, Wnt/β-catenin, and PI3K/Akt/mTOR signaling pathways - Nour Y.S. Yassin (Elsevier, 2022)
Hepatocellular carcinoma (HCC) has been identified as one of the most deadly malignancies with limited therapeutic efficacy worldwide. However, understanding the molecular mechanisms of crosstalk between signaling pathways in HCC and predicting cancer cell responses to targeted therapeutic interventions remain to be challenge. Thus, in this study, we aimed to evaluate the anticancerous efficacy of Silybum marianum total extract (STE), silymarin (Sm), and silibinin (Sb) against experimentally-induced HCC in rats. In vitro investigations were also performed and the anticancer effects against HCC cell lines (HepG2 and Huh7) were confirmed. Wistar rats were given diethylnitrosamine (DEN)/2-acetylaminofluorene (AAF)/carbon tetrachloride (CCl4) and were orally treated with STE (200 mg/kg body weight (bw)), Sm (150 mg/kg bw), and Sb (5 mg/kg bw) every other day from the 1st or 16th week to the 25th week of DEN/AAF/CCl4 injection. Treatment with STE, Sm, and Sb inhibited the growth of cancerous lesions in DEN/AAF/CCl4-treated rats. This inhibition was associated with inhibition of Ki-67 expression and repression of HGF/cMet, Wnt/β-catenin, and PI3K/Akt/mTOR signaling pathways. STE, Sm, and Sb improved liver function biomarkers and tumor markers (AFP, CEA, and CA19.9) and increased total protein and albumin levels in serum. STE, Sm, and Sb treatment was also noted to reduce the hepatic production of lipid peroxides, increase hepatic glutathione content, and induce the activities of hepatic antioxidant enzymes in DEN/AAF/CCl4-treated rats. These results indicate that STE, Sm, and Sb exert anti-HCC effects through multiple pathways, including suppression of Ki-67 expression and HGF/cMet, Wnt/β-catenin, and PI3K/Akt/mTOR pathways and enhancement of antioxidant defense mechanisms.